ANALYSIS OF SHARIA ACCOUNTING PRACTICES IN THE MANAGEMENT OF PANAI FUNDS (DUI BALANCA) IN BUGIS CUSTOMARY TRADITIONS, SUPPA DISTRICT, PINRANG REGENCY - -, Ipa Trihapsari; Nurhayati, St.; Rismala (Islamic Financial And Accounting Review, 2024)
Panai money (dui balanca) in Bugis tradition refers to a sum of money given by the prospective groom to the prospective bride’s family as part of the marriage process, based on mutual agreement between the two extended families. This money is fully managed by the prospective bride’s family and serves not only as a symbol of commitment in the marital relationship but also as a form of respect toward the bride’s family. This study employs a descriptive qualitative method with a phenomenological approach. The primary data were obtained directly through interviews with married individuals, their parents, and community leaders in Suppa District. Secondary data were gathered from books, official documents, and previous research (journals or theses) relevant to the topic. The data analysis techniques used include data reduction, data display, and conclusion drawing/verification. The findings reveal two key points. First, the management of panai money in the Bugis community of Suppa District is directly handled by the prospective bride. The amount of panai money given by the groom’s family to the bride’s family is determined through a mutual agreement. The principle of fairness in determining the panai amount is highly upheld by the community to prevent disputes between the two parties. Second, based on the research findings, the practice of sharia accounting in the management of panai money has not yet fully implemented the principles of transparency and accountability. The community's understanding of sharia accounting varies significantly, depending on factors such as educational background, access to information, and prior experience with sharia-based financial practices.